Potential discovery of staus through heavy Higgs boson decays at the LHC - Arganda Carreras, Ernesto (2018)
In this work we present a new search strategy for the discovery of staus at the LHC in the context of the minimal supersymmetric standard model. The search profits from the large s-channel b-quark annihilation production of the heavy CP-even and CP-odd Higgs bosons (H/A) which can be attained in regions of tan β ≫ 1 that avoid the stringent H/A → τ⁺ τ⁻ searches via decays into stau pairs. We also focus on regions where the staus branching ratios are dominated by the decays into a tau lepton and the lightest neutralino. Thus the experimental signature consists of final states made up of a tau-lepton pair plus large missing transverse energy. We take advantage of the large stau-pair production cross sections via heavy Higgs boson decays, which are between one or two orders of magnitude larger than the usual electroweak production cross sections for staus. A set of basic cuts allow us to obtain significances of the signal over the SM backgrounds at the discovery level (5 standard deviations) in the next LHC run with a center-of-mass energy of 14 TeV and a total integrated luminosity of only 100 fb-1.